The Application of Pearls in Traditional Medicine of China and Their Chemical Constituents, Pharmacology, Toxicology, and Clinical Research - Song, Yinglian; Chen, Wanyue; Fu, Ke; Wang, Zhang (Frontiers in Pharmacology, 2022)
Although pearls are well known by most people, their medicinal value has not been popularized. This article collates the medicinal history of pearls over 2,000 years in China, including the application of pearls in the traditional medicine of China and their various preparations, as well as the progress of their chemical constituents, pharmacology, toxicology, and clinical research. Pearls from three different sources are used as medical materiel by 9 nationalities and 251 prescription preparations in China. In addition, pearls contain various inorganic constituents, such as calcium carbonate, trace elements, and water, and organic constituents, such as amino acids. In terms of pharmacology, pearls have many effects such as calming, improving cognitive ability, being anti-epileptic, promoting bone growth and regeneration, promoting the proliferation and migration of human microvascular endothelial cells, protecting the heart, anti-hemolysis, and anti-oxidation. In terms of toxicology, pearls are safe to take for a long time without exerting obvious adverse reactions. In terms of clinical application, pearls have been used to treat many diseases and conditions, such as convulsions, epilepsy, palpitations, eye diseases, ulcer diseases, skin diseases, or skin lesions. This article provides a reference for the application and research of pearls in the future.